2012
DOI: 10.4103/0974-620x.94763
|View full text |Cite
|
Sign up to set email alerts
|

Childhood microbial keratitis

Abstract: Purpose:To evaluate risk factors for pediatric microbial keratitis and to describe the clinical picture, microbial spectrum, treatment modalities, posttreatment sequelae, and visual outcome in cases with pediatric microbial keratitis.Materials and Methods:All cases of microbial keratitis that occurred in children 16 years or younger who had an initial examination between January 2000 and December 2010 at a tertiary referral eye hospital in Riyadh, Saudi Arabia, were identified. A retrospective review of medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
30
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 16 publications
9
30
4
Order By: Relevance
“…Comorbidities were present in 5.8% of the study patients; this was lower than rates reported in previous studies (3,(8)(9)(10)(11)(12)(13)(14) . Cancer was the main comorbidity, present in 2% of our records.…”
Section: Discussioncontrasting
confidence: 51%
See 4 more Smart Citations
“…Comorbidities were present in 5.8% of the study patients; this was lower than rates reported in previous studies (3,(8)(9)(10)(11)(12)(13)(14) . Cancer was the main comorbidity, present in 2% of our records.…”
Section: Discussioncontrasting
confidence: 51%
“…The prevalence of microorganisms responsible for microbial ke ratitis in children and adolescents varies in different regions of the world (3) . Microbial cultures were positive in 40.3% of the study sample, whereas in the literature positivity has ranged from 33% to 87% (3,(8)(9)(10)(12)(13)(14)(15)(16)(17)(18)20,29) . Polymicrobial isolates accounted for 9.5% of positive cultures in our study.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations